PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN COMPUTATIONAL THINKING SISWA SEKOLAH DASAR - Nuri Noviyanti; Yeni Yuniarti; Triana Lestari (Program Studi PGSD Universitas Flores, 2023)
Education Transformation in Indonesia is now demanded to be faster and able to produce students who are not only proficient in reading and writing but also students who have skills in matters directly related to problem solving in real life. The ability to think critically, apply creativity, work together, solve problems and be communicative are some of the abilities that are the main capital in 21th Century Learning besides other abilities such as reading, writing science and mathematics. The purpose of this study is in accordance with the existing problem formulation, namely to determine the effect of differentiated learning on the computational thinking abilities of elementary school students. In this study the authors used a quantitative approach with quasi-experimental research methods. The research design used was Time Series Design Intervention Analysis. The selection of the method and design of this study took into account the implementation of repeated treatments. The results of testing the hypothesis using the paired sample t-test from the pre-test and post-test data in series 1, 2, and 3 show the results t-count> t-table. In the series one t-count obtained is 7.319. In series 2 the t-count got a value of 9.729 and in series 3 the t-count was 11.660. The results obtained were that the Computational Thinking ability of elementary school students had increased after being treated with Differentiated Learning.